INJURY RATES, MECHANISMS, AND RISK FACTORS FOR INJURY IN YOUTH ROCK CLIMBERS. Issue 7 (11th March 2014) - Woollings, K; McKay, C; Kang, J; Meeuwisse, W; Emery, CA
Abstract : Background: Participation in rock climbing has grown globally in recent years. In 2010, the International Federation of Sport Climbing was officially recognized by the International Olympic Committee as part of the Olympic Family. Although some studies exist describing adult sport climbing injuries, few have examined injury in youth climbers. Objective: To examine incidence, mechanisms, and risk factors for injury in 11- to 19-year-old recreational and elite sport climbers and boulderers. Design: Cross-sectional study design. Setting: Elite and recreational youth climbers were recruited from climbing facilities across Alberta, Canada. Participants: Male and female climbers, aged 11-19 years, recruited from competitive junior teams and from recreational programs at each gym. In total, 285 participants were approached and 116 (41%) completed an anonymous questionnaire. Risk factor assessment: Potential risk factors included climbing level, age, sex, height, weight, grade at which subjects climbed, injury in a sport other than climbing, risk-taking behaviours, socioeconomic status, climbing disciplines performed, participation in sports other than climbing, helmet use, preventive taping, use of cool-down, and climbing exposure hours. Main outcome measurements: The primary outcome measure was climbing injury. Medical attention injuries and injuries resulting in time loss from climbing were also measured. Results: The incidence rate of climbing injury was 4.44 injuries/1000 climbing hours (95% CI; 3.74, 5.23). Sprains and strains were the predominant injury type, and the primary mechanism of injury was repetitive overuse, followed by falls. Hands and fingers were the most commonly injured locations. Older age (15–19-year-olds), injury in a sport other than climbing, and preventive taping were shown to be risk factors for injury. Conclusions: Climbing injury incidence rates are high in youth climbers. Findings are consistent with climbing injury studies in adults. Potential modifiable risk factors warrant further investigation in order to inform development of future injury prevention strategies.